Comparison of Ultrasound-Guided and Palpation Techniques for Radial Artery Cannulation - Sapkota, Sudip; Maharjan, Shyam Krishna; Gurung, Prashansa; Suwal, Allen (Nepal Journal of Multidisciplinary Research, 2025)
Background: Radial artery cannulation is a routine procedure performed in operating rooms and intensive care units for continuous blood pressure monitoring and arterial blood gas analysis. Among the various techniques available, ultrasound-guided (USG) and palpation methods are commonly used. This study aimed to compare the success rate, average time for successful cannulation, first-attempt success rate, and complication rates between the USG-guided and palpation techniques for radial artery cannulation. Methods: A comparative cross-sectional study was conducted at Kathmandu Medical College Teaching Hospital, involving 52 patients aged 19 to 77 years with American Society of Anesthesiologists (ASA) physical status I–IV undergoing major surgery. Participants were randomly allocated into two equal groups. In Ultrasound group cannulation using ultrasound guidance, similarly in palpation group cannulation performed by the palpation method. Demographic characteristics, baseline vital signs, time required for successful cannulation, number of attempts, success or failure, and complications (mainly hematoma) present or absent were noted. Results: There were no significant differences in demographic characteristics or baseline vital signs between the groups. The overall success rate was identical in both groups (96.2%vs 96.25) and was not statistically significant (p>0.05). Average time for successful cannulation were similar (59sec vs 60sec) (p = 0.808). There was higher first attempt success rate in ultrasound group compared with palpation. {(61.8% vs. 30.8%) P=0.026}.The median number of attempts for successful cannulation were less in USG guided group compared to palpation group i.e. {1(1, 2) vs. 2(1,3)} (p=0.024).There were fewer underlying hematoma in ultrasound guided group i.e. 11.5% vs. 30.8% but that was statically non-significant (p=0.090). Conclusion: In our study, there was similar time duration for successful cannulation and overall success rate for both groups. However, there was a higher first attempt success rate, the fewer number of cannulation attempts in ultrasound guided method compared to the palpation method. Novelty: This study highlights the clinical advantage of ultrasound guidance in improving the efficiency of radial artery cannulation by increasing the likelihood of first-attempt success and reducing the number of attempts, supporting its wider adoption in perioperative and critical care settings.